The role of high-resolution manometry in the diagnosis of esophageal disorders (literature review and personal clinical observations) - Yu.M. Stepanov; N.V. Prolom; S.O. Tarabarov; O.M. Babii; I.M. Adamska (Gastroenterologìa, 2025)
At present, clinical gastroenterology utilizes a number of high-precision methods for functional diagnosis of the esophagus and stomach, among which high-resolution manometry (HRM) holds a prominent place. This innovative technique enables a detailed assessment of esophageal function, particularly the coordination of muscular contractions during swallowing and the effectiveness of the lower esophageal sphincter. HRM has established itself as an exceptionally effective method for detecting motor disorders such as achalasia, gastroesophageal reflux disease, diffuse esophageal spasm, as well as other functional abnormalities that may cause dysphagia or impair bolus transit. One of the key advantages of this technique is the use of high-density catheters equipped with numerous pressure sensors spaced approximately 1 cm apart. This allows for the creation of detailed topographic maps of pressure in the esophagus, which display real-time muscle contractions and peristaltic activity. The high spatial and temporal resolution of HRM makes it possible to identify even minimal motor abnormalities that previously remained undetected when using conventional diagnostic methods. A significant advancement offered by HRM is the improved diagnosis of achalasia, particularly through its differentiation into three relevant subtypes. This classification has direct clinical implications, as it enables the personalization of treatment strategies based on the specific subtype of disorder. In the context of gastroesophageal reflux disease, HRM allows for precise assessment of the lower esophageal sphincter function and diaphragmatic contribution, which is crucial for detecting weakness of the antireflux barrier. Additionally, the method facilitates the identification of coexisting peristaltic disorders, which may reduce esophageal ability to clear from refluxate effectively, thereby aggravating the clinical presentation of the disease. In summary, high-resolution manometry plays a central role among modern diagnostic tools in gastroenterology, offering high accuracy in identifying esophageal motor dysfunctions and contributing to the optimization of therapeutic strategies. Ultimately, this leads to improved patient outcomes and quality of life, enabling clinicians to make informed decisions based on objective functional assessments of the esophagus.